2005
DOI: 10.1179/174367605225011016
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite covered polymer derived ceramic foams: novel hierarchical pore systems for sorption and catalysis

Abstract: Open cell polymer derived ceramic foams were prepared by a self-foaming process of a filler loaded poly(silsesquioxane) and subsequent pyrolysis at 1000uC in nitrogen atmosphere. A 1 : 1 mixture by weight of elemental Si and SiC was introduced as particulate filler. Foam samples without and with addition of a small amount (1 . 5 wt-% ) of Cu 2 O were prepared. Open cell ceramic foams with average cell diameter of 0 . 5-1 . 5 mm, compressive strength of up to 3 MPa and porosity of up to 90% were used as support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…While the study of composite materials has largely been dominated by a focus on dense materials [2,3], porous composite materials have recently attracted considerable attention and have been identified for promising applications as bone scaffolds in biomedicine [4][5][6][7][8][9][10]; shielding layers in electrical engineering [11,12]; shock dissipators in structural engineering [13]; and as catalysts and filters in chemical engineering [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…While the study of composite materials has largely been dominated by a focus on dense materials [2,3], porous composite materials have recently attracted considerable attention and have been identified for promising applications as bone scaffolds in biomedicine [4][5][6][7][8][9][10]; shielding layers in electrical engineering [11,12]; shock dissipators in structural engineering [13]; and as catalysts and filters in chemical engineering [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon powder can be used to obtain Si-rich zeolites such as MFI-type zeolite (which is an important catalyst for isomerization reactions, for the decomposition of nitric oxides, and also for partial oxidation reactions) after a hydrothermal treatment in the presence of a structure-directing agent (SDA) Scheffler 2006, 2008). By 29 Si-MAS NMR spectroscopic investigations, it could be shown that the silicon filler in the starting mixture is transformed into the zeolite coating during the hydrothermal treatment (Scheffler et al 2005a). Al-rich zeolites, which are important components in hydrocracking catalysts as well as in separation processes such as pressure or temperature swing air separation, might be obtained by the partial transformation of PDC foams filled with Al powder as shown in Fig.…”
Section: Zeolite-coated Pdc Foamsmentioning
confidence: 98%
“…An abundance of research has been published recently regarding preceramic polymer foams as potential materials for ceramic filters, catalytic supports, thermal insulation, and lightweight structural reinforcements (Scheffler et al 2005a, Scheffler andColombo 2005;Zeschky et al 2003). Because of their natural foaming ability upon cross-linking, many preceramic polymers are suitable for direct foaming yielding macroporous components.…”
Section: Precursor or Polymer-derived Ceramicsmentioning
confidence: 99%
“…The foaming process of those open-cellular materials from silicone resins was developed for the manufacture of ceramic foams and is described in ref. [22][23][24] As photocatalytic active filler particles Aerosol TiO 2 P25 (Degussa GmbH, Hanau, Germany) with a specific surface area of 50 AE 15 m 2 Á g À1 and an average particle size d 50 of 21 nm was used.…”
Section: Materials Processingmentioning
confidence: 99%